Evaluation of Microtraining Modifications: Implications for Para- professional Training - Uhlemann, Max R.; Stone, Gerald R.; Evans, David R.; Hearn, Margaret T. (Canadian Journal of Counselling and Psychotherapy, 2012)
This study assessed the viability of a modified microtraining approach to par- aprofessional development using programmed manuals and models. Training and evaluation took place within a community counselling setting with therapeutic workers randomly assigned to a Model group (6), No-Model group (6), and a Control group (8). Both training groups (Model; No-Model) were exposed to the same learning (programmed manuals) and practice phases while the addition of models differentiated the groups. Covariance analyses indicated that training groups emitted fewer closed inquiries and had a higher interview empathy performance than a no-training group. Participants did not substantially differ on written empathy, but the No-Model participants emitted more open-inquiries at posttest than Control participants. These effects seem to be primarily a function of the differences between training and no-training with little effect due to modeling. Results were discussed in terms of the differences between knowledge and performance competencies and the relationship between specific skills and empathie communication. Implications for expanded dimensions of skill development programs and the usefulness of programmed learning were also raised while acknowledging the limitations of this study.